Cryptosporidium erinacei and C. parvum in a group of overwintering hedgehogs - Hofmannová, Lada; Hauptman, Karel; Huclová, Kristýna; Květoňová, Dana; Sak, Bohumil; Kváč, Martin (European journal of protistology, 2016)
This study describes cryptosporidiosis in an overwintering group of 15 European hedgehogs (Erinaceus europaeus), comprising 3 adults and 12 juveniles. Four juvenile hedgehogs were hospitalised with anorexia, malodorous diarrhoea and dehydration. Immediate parasitological examinations revealed the presence of Cryptosporidium sp. in these animals and also in 5 other juveniles. All hedgehogs were coproscopically monitored for 4 months over the winter season. Shedding of Cryptosporidium oocysts persisted from 6 to 70 days. Repeated shedding of Cryptosporidium oocysts occurred in 3 animals after 4 months subsequent to the first outbreak. Clinical signs were observed only at the beginning of the outbreak (apathy, anorexia, general weakness, mild dehydration, and malodorous faeces with changed consistence - soft/diarrhoea) in the 4 hospitalised juveniles. Overall 11 hedgehogs were Cryptosporidium-positive, both microscopically and by PCR methods. Sequence analyses of SSU rRNA and gp60 genes revealed the presence of C. parvum IIdA18G1 subtype in all positive hedgehogs. Moreover, 3 hedgehogs had a mixed infection of the zoonotic C. parvum and C. erinacei XIIIaA19R13 subtype. Cryptosporidium infections can be rapidly spread among debilitated animals and the positive hedgehogs released back into the wild can be a source of the infection for individuals weakened after hibernation.
Keywords: Animals; ježkovití; Female; feces; Feces; Genes, rRNA; Hospitals, Animal; ženské pohlaví; Cryptosporidium parvum; Cryptosporidiosis; nemocnice veterinární; Hedgehogs; Phylogeny; Male; kryptosporidióza; geny rRNA; zvířata; mužské pohlaví; fylogeneze; Cryptosporidium